Long‐term patterns in interpersonal behaviour amongst psychopathic patients in secure inpatient treatment: A follow‐up study. (26th January 2015) - Draycott, Simon; Short, Roxanna; Kirkpatrick, Tim
Abstract Psychopathy is a disorder that is partly defined by with maladaptive interpersonal behaviour and has significant effects on treatment outcomes. A previous study (Draycott et al., 2011) found that higher levels of psychopathy led to a specific interpersonal 'trajectory' amongst patients in a secure psychiatric treatment programme during the first 9 months of their admission. In that programme, more psychopathic patients became increasingly dominant over time, and less psychopathic patients became increasingly hostile. This study is a longer‐term follow‐up and extension of that study, extending the window of observation to 33 months of treatment. It was found that the more psychopathic patients' increased dominance returned to baseline levels by 33 months, as did the less psychopathic patients' increased hostility. This suggests that treatment for this group is not idiopathic but leaves unanswered the question as to what these divergent trajectories represent. Copyright © 2015 John Wiley & Sons, Ltd.